Vendor satisfaction of E-government procurement systems in developing countries: an empirical research in Indonesia. Issue 3 (3rd July 2018) - Seo, DongBack; Tan, Chee-Wee; Warman, Gumala
ABSTRACT: Adoption of e-government services persists as a prime concern among scholars and practitioners. Although much progress has been attained in comprehending how e-government services have been adopted by citizens, our understanding of vendors' willingness to engage in Government-to-Business transactions (e.g. e-procurement) is much more limited by comparison, especially from the perspectives of service convenience and performance failure. For this reason, there have been increasing calls for further investigations into the factors affecting vendors' adoption of e-government services and especially those operating in developing countries. Drawing on the compatibility principle, we advance a theoretical model that posits performance failure of e-government systems as object-based beliefs affecting vendors' behavioral-based belief of service convenience. Upon analyzing survey data gathered from 227 vendors based in Indonesia on their experiences with e-government procurement systems, we discover that vendors' evaluations of service convenience are negatively influenced by the presence of information, function, and system failures and that the effects of these failures vary across different dimensions of service convenience. In turn, service convenience and performance failure exert opposite impact on vendors' satisfaction with e-government systems.